Pengaruh Penempatan karyawan, Beban kerja, Burnout, Keterlibatan Karyawan, Pengembangan Karier dan Komitmen Organisasi terhadap Keinginan Keluar Karyawan (Studi pada Karyawan medical representative Industri Farmasi di Sulawesi Utara) - Datu, Jusak S.; Habsji, Taher Al; Nimran, Umar; Idrus, Syafeii (Universitas Brawijaya, Indonesia, 2011)
All investments made by companies, to those who possess the qualified and competence would be in vain when the employee left the company, to reduce the risk of losing potential employee, an effort should be made to the company by building on existing documents within a company. This study is expected to know the influence of each variable in the Intention to leave in efforts to maintain employee not expensive, so do not be a burden to corporale overhead costs. The purpose of this study to assess the relationship between Job Placement (X) Workload (X), Burnout (X), Job Involvement (x,), Career Development (7), Organizational commitments (Y) Intention to leave (Y). Data analysis using Structural Equations Modeling (SEM). samples is 192 employees in medical representatives of the pharmaceutical industry in North Sulawesi. The results of this study found that career development and burnout can affect the intention to leave through career development and organizational commitment workload will affect the Intention to leave through career development. Employee involvement influence the Intention to leave through the organizational commitment.